V.I. Lenin (on the left)in the Kremlin grounds taking a walk after recovery from being wounded. Compare: 69/39 A, page 81 - Savel'ev, A.I.
V.I. Lenin (on the left)in the Kremlin grounds taking a walk after recovery from being wounded. Compare: 69/39 A, page 81.